Transformation Toward Entrepreneurial University: Enhancing the Sustainability of Private Universities Through Soft System Methodology - Indah Kusuma Hayati; Muhammad Syamsul Maarif; Illah Sailah; Nimmi Zulbainarni (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Private universities in Indonesia play an important role in widening access to higher education and contributing to national development. At the same time, many of these institutions operate under conditions of limited financial resources, human capacity, and infrastructure, while facing increasing competition. These challenges place pressure on their long-term competitiveness and sustainability.Purpose: This study explores how private universities may move toward an entrepreneurial university orientation by examining key factors and managerial practices that support competitiveness, sustainability, and socio-economic contribution.Design/methodology/approach: The study adopts a qualitative approach based on Soft Systems Methodology (SSM) to examine complex institutional change involving multiple stakeholders. Data were drawn from a review of relevant literature and interviews with selected experts.Finding/Results: The study shows that efforts to move toward an entrepreneurial university are shaped by how academic, innovation, and entrepreneurial activities are brought into relation with one another. When these activities begin to interact more consistently, they create conditions that support the development of innovation and entrepreneurial initiatives linked to institutional sustainability.Conclusion: The analysis suggests that changes toward an entrepreneurial orientation in private universities tend to be associated with leadership practices, governance arrangements that allow adaptation, and the gradual formation of an innovation-oriented culture. How human resources are developed, curricula are adjusted, collaborative relationships are built, and monitoring processes are carried out appears to influence the sustainability and competitiveness of these institutions over time.Originality/value: This study offers a context-specific framework for Indonesian private universities and provides practical insights for institutional leaders seeking to enhance innovation capacity and long-term sustainability.      Keywords:  academic ecosystem, entrepreneurial university, entrepreneurship ecosystem, innovation ecosystem, private university